The teachings of Hurufism and Nasimi’s poetic skills - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
The article describes the stages of the formation and development of the Hurufian order and the influence of this mystical direction on the work of Imadiddin Nasimi. In addition, comments related to the uniqueness of Nasimi’s style and themes are noted. Poems of the poet on various topics were subjected to ideological-artistic analysis. It is also based on the fact that Nasimi’s poetry was a source of inspiration for the work of many poets. Based on the analysis, scientific conclusions related to the topic were expressed. Key words: Imadiddin Nasimi, Hurufism, calligraphy, Arabic letters, literary influence, artistic skills